Synthesis and Antimicrobial Activity of Novel Derivatives of 7‐aryl‐10‐thioxo‐7, 10, 11, 12 – tertahydro‐9H‐benzo[H] pyrimido [4, 5‐b] quinoline‐8‐one. (10th January 2018) - Kumbhar, Digambar; Chandam, Dattatray; Patil, Reshma; Jadhav, Sunetra; Patil, Dayanand; Patravale, Ajinkya; Deshmukh, Madhukar
Abstract : A highly competent synthesis of novel 7‐aryl‐10‐thioxo‐7, 10, 11, 12‐tertahydro‐9 H ‐benzo [ H ] pyrimido [4, 5‐ b ] quinoline‐8‐one derivatives has been reported through a Knoevenagel condensation followed by Michael addition and subsequent cyclization using ethanol:acetic acid (8:2  v /v). The mentioned protocol has advantages like high yields, cleaner reactions, operational simplicity, and environment friendliness. Moreover, these compounds were further screened against the plant pathogenic fungi like Colletotrichum truncatum, U stilago maydis, Trichosporon, Trichothecium sp ., Aspergillus oryze, Aspergillus terreus, and Aspergillus niger by agar well method bioassay. The results were elaborated for minimum inhibitory concentration determination using agar dilution method against fungal strains C. truncatum and U. maydis as well as broth dilution method for bacteria species Gram‐positive Bacillus megaterium and Gram‐negative Proteus vulgaris . Most of the tested compounds showed promising results towards the antimicrobial activity. Abstract :